Nonsurgical Modalities for Treatment of Early-stage Lung Cancer. Issue 2 (March 2015) - Campbell, Sabrina; Rubio, Edmundo; Ie, Susanti; Boyd, Michael
Abstract : For patients with early-stage non–small cell lung cancer, the gold standard of treatment remains surgery. The natural history of patients with early-stage lung cancer who do not undergo any treatment has been retrospectively reviewed and despite identification of lung cancer at it earliest stages, survival is poor in patients who do not undergo treatment. For patients who decline or are deemed too high risk for surgery conventional radiation therapy has been the preferred nonsurgical approach, but local control rates remain low when compared with surgical resection. There have been ongoing advances in nonsurgical treatment approaches for early-stage non–small cell lung cancer. Knowledge of the various nonsurgical modalities, their effectiveness, and risks is needed to provide each patient with the most appropriate, effective, and advanced care.